An MMP-2 sensitive and reduction-responsive prodrug amphiphile for actively targeted therapy of cancer by hierarchical cleavage. Issue 7 (3rd January 2023) - Zhang, Xueni; Dai, Lihui; Ding, Yumeng; Liu, Qian; Li, Xiaoya; Liu, Mengting; Meng, Meng; Pan, Jie; Xi, Rimo; Yin, Yongmei
Abstract : Novel dual-stimuli responsive prodrug amphiphile-based micelles for actively targeted cancer therapy through hierarchical cleavage. Abstract : A hierarchically cleaved amphiphile, mPEG-pep-etcSS-CPT, was synthesized to pursue actively targeted cancer therapy through self-assembly. This micelle can respond to MMP-2 achieving dePEGylation and releasing RGD peptides to be internalized into targetable tumor cells. Inside the cell, free CPT could be released by reduction-response leading to cytotoxicity.